APPLICATION LOVE LANGUAGE: WORDS OF AFFIRMATION IN FRIENDSHIP RELATION - Fernando, Farhan; Herdiawati, Cut Dhien; Nurjannah, Esa Noviana; Lestari, Aghnia Dian (Green Publisher Indonesia, 2024)
There are forms of communication in establishing a friendly relationship. Friendship is one of the sources of support in living everyday life. Love language and interpersonal communication have a close relationship in the context of understanding and strengthening relationships between individuals. The language of love is often articulated with expressions of fondness, love and affection. One of the love languages is words of affirmation which are affirmative words given to friends. This research aims to find out how the form of application of words of affirmation in the scope of friendship and find out the development of friendship relationships, especially in words of affirmation. This research uses descriptive qualitative methods through observation, interview and documentation data collection techniques. Researchers used the interpersonal communication approach by DeVito with 7 indicators (openness, empathy, positiveness, immideacy, interaction management, expressiveness, orientation to others). The results of this research analysis found that the use of positive and supportive communication can strengthen the emotional bond between couples. This shows that the use of impressive words, appreciation, and support is an important foundation in strengthening the emotional bond between relations.